Hydroxymethanesulfonate formation as a significant pathway of transformation of SO2. (1st February 2023) - Zhang, Hailiang; Xu, Yongfu; Jia, Long
Abstract: The transformation mechanism of sulfur dioxide (SO2 ), especially during haze periods, is unclear, and hydroxymethanesulfonate (HMS) formation is recently recommended to be one of the important pathways for the conversion of SO2, while detailed laboratory studies under different ionic strength conditions are still lacking. Here we have experimentally discovered that the formation rate constant of HMS in bulk water and aerosol water is significantly influenced by the ionic strength, which is about 2–3 orders of magnitude larger in aerosol water but about 2 orders of magnitude smaller in cloud and fog than previously recognized. The HMS formation rate even exceeds the sulfate formation from oxidation of dissolved SO2 by H2 O2 in aerosol water with a pH larger than 5.1. This study provides an explanation for the elevated particulate sulfur formation rate during winter haze periods. Highlights: Hydroxymethanesulfonate (HMS) formation rate is influenced by ionic strength. HMS formation in aerosol is 2–3 orders of magnitude larger than previously recognized. HMS accounts for larger than 7.8% of particulate sulfur in aerosol water with pH > 4.5.